Mortality after total hip replacement surgery: A systematic review. Issue 6 (June 2014) - Berstock, J. R.; Beswick, A. D.; Lenguerrand, E.; Whitehouse, M. R.; Blom, A. W.
Abstract : Total hip replacement causes a short-term increase in the risk of mortality. It is important to quantify this and to identify modifiable risk factors so that the risk of post-operative mortality can be minimised. We performed a systematic review and critical evaluation of the current literature on the topic. We identified 32 studies published over the last 10 years which provide either 30-day or 90-day mortality data. We estimate the pooled incidence of mortality during the first 30 and 90 days following hip replacement to be 0.30% (95% CI 0.22 to 0.38) and 0.65% (95% CI 0.50 to 0.81), respectively. We found strong evidence of a temporal trend towards reducing mortality rates despite increasingly co-morbid patients. The risk factors for early mortality most commonly identified are increasing age, male gender and co-morbid conditions, particularly cardiovascular disease. Cardiovascular complications appear to have overtaken fatal pulmonary emboli as the leading cause of death after hip replacement. Cite this article: Bone Joint Res 2014;3:175–82